Bauran Pemasaran Terhadap Keputusan Pembelian Konsumen pada PT. Mekada Abadi - Agnes Febrianne Yauandi; Januardin Januardin; Feny Cau; Geovanny Geovanny; Feren Wong (Journal of Management and Bussines (JOMB), 2023)
This study aims to examine and analyze the effect of price, promotion, service quality on purchasing decisions at PT Mekada Abadi. The decline in job satisfaction can be seen from employees who resign from the company. The research method used is a quantitative method with a descriptive type and the nature of the research is causal. The sample used was 103 people. Methods of data analysis using multiple linear regression. Simple random sampling was used as the sampling method. The results showed that the partial test on the price variable with value (2.552 > 1.976), promotion (3.289 > 1.976) and quality of service (5.296 > 1.976) partially had a positive and significant effect on purchasing decisions at PT Mekada Abadi. In the F test, the price, promotion and service quality variables show a positive and significant effect with a value (25,636 > 3.09) on purchasing decisions at PT Mekada Abadi. In conclusion, the elements of the marketing mix, namely price, promotion and service quality have a positive and significant effect on purchasing decisions. Keywords : Price, Promotion, Service Quality and Purchase Decision